Enhancing SME Performance through Entrepreneurial Literacy, Innovation, and Market Responsiveness: The Mediating Role of Digital Transformation - Mutinda Teguh Widayanto; Raihan Wishal Nafis (Universitas Islam Nahdlatul Ulama Jepara, 2025)
Objective: This study aims to examine how entrepreneurial literacy, innovation, and market responsiveness influence the performance of Small and Medium Enterprises (SMEs), with digital transformation acting as a mediating variable. The research focuses on SMEs in East Java, Indonesia, where SMEs are pivotal to regional economic development. Research Design & Methods: A quantitative research design was adopted, involving the distribution of structured questionnaires to 200 SME owners and managers across five districts in East Java. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4 to assess both direct and indirect relationships among the variables. Findings: The results show that innovation, market responsiveness, and digital transformation have significant direct effects on SME performance. Entrepreneurial literacy does not have a direct influence; however, its effect becomes significant when mediated by digital transformation. Digital transformation acts as a complementary mediator of both innovation and market responsiveness on performance. Implications & Recommendations: The findings suggest that SME development strategies should integrate digital adoption with entrepreneurial and innovation training. Policymakers and business support institutions are encouraged to promote programs that build digital capabilities as a means to strengthen SME competitiveness and resilience in the post-pandemic era. Contribution & Value Added: This research offers a comprehensive conceptual model that positions digital transformation as a critical internal enabler of SME performance. It contributes to the entrepreneurship and SME literature by combining entrepreneurial literacy, innovation, and market responsiveness within a unified framework, particularly in the context of emerging economies.